PENGARUH BRAND FAMILIARITY DAN PERCEIVED QUALITY TERHADAP REPURCHASE INTENTION - Nugraha, Ikhlas Mufti (Journal of Business Management Education (JBME), 2020)
The purpose of this research is to find out the influence of brand personality on purchase intention in member of Female Dailty in Indonesia. A total of 200 respondents were using probability sampling. A questionnaire was used a research instrument to collect data from respondents. The analisis technique used is a verification technique using of structure equation model (SEM). The research shows that brand personalityÂ  and social media marketing has an influence on purchase intention.